2016
DOI: 10.1007/s10661-016-5750-0
|View full text |Cite
|
Sign up to set email alerts
|

Compositing climate change vulnerability of a Mediterranean region using spatiotemporally dynamic proxies for ecological and socioeconomic impacts and stabilities

Abstract: The study presents a new methodology to quantify spatiotemporal dynamics of climate change vulnerability at a regional scale adopting a new conceptual model of vulnerability as a function of climate change impacts, ecological stability, and socioeconomic stability. Spatiotemporal trends of equally weighted proxy variables for the three vulnerability components were generated to develop a composite climate change vulnerability index (CCVI) for a Mediterranean region of Turkey combining Landsat time series data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In the study, the GWP areas in the Alaşehir sub-basin were determined by using a multi-criteria approach, in other words, a weighted image overlay method that focuses on a GIS method integrated with RS (Demirkesen and Evrendilek 2017), and the accuracy and efficiency of the results obtained at the end of the study were checked. In this context, the data used, the sources of the data, and the procedures applied to the data are summarized in Fig.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the GWP areas in the Alaşehir sub-basin were determined by using a multi-criteria approach, in other words, a weighted image overlay method that focuses on a GIS method integrated with RS (Demirkesen and Evrendilek 2017), and the accuracy and efficiency of the results obtained at the end of the study were checked. In this context, the data used, the sources of the data, and the procedures applied to the data are summarized in Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…The area chosen for the study is the Alaşehir sub-basin, located in the Gediz River basin in western Turkey, because this area has a rich GWP with an aquifer under fertile agricultural alluvial soils and it is also under the GWPR due to industrial settlements over there. This study involves the determination of the GWP by considering multi-proxies as multi-criteria used by a weighted image overlay analysis (Demirkesen and Evrendilek 2017). A multicriteria evaluation approach is required to incorporate more than one proxy into the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Increased human health vulnerability to climate change is associated with many factors including rapid population growth, (as in the case of China) poverty and hunger, poor health, low levels of education, and lack of access to information on climate change (Demirkesen and Evrendilek 2017;Füssel and Klein 2006). It has been shown that the elderly (people who are 65 years or older) are particularly vulnerable to the impacts of heat waves (Li et al 2017b).…”
Section: <>mentioning
confidence: 99%
“…A number of rivers, canals and creeks are spread over this division forming like a net. The area is vulnerable to cyclone, flood, drainage congestion, river erosion, and river sedimentation [12] [13]. Main rivers are Arial Kha, Bishkhali, Burishwar, Tentulia, Paira, Haringhata, Baleshwar, Kirtankhola, Katcha Lohalia and Agunmukha.…”
Section: Introductionmentioning
confidence: 99%